Matthias Flacius Illyricus: a disciple of Luther = MATTHIAS FLACIUS ILLYRICUS : UM DISCÍPULO DE LUTERO - Ilić, Luka (Ciências da religião história e sociedade, 2007)
This article presents a brief introduction to life and work of Matija Vlaˇci ́c Ilirik (the Latin form of his name is Matthias Flacius Illyricus), a Croatian born Lutheran reformation of sixteenth century. Some bio-graphical data are presented, as well as the main themes of Flacius’ theological thought. This article therefore is a contribution to the field of sixteenth century studies.